Introducing environmental variables in nonparametric frontier models: A probabilistic approach - Cinzia Daraio; Léopold Simar (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2003)
This paper proposes a general formulation of a nonparametric frontier model introducingexternal environmental factors that might influence the production process butare neither inputs nor outputs under the control of the producer. A representation isproposed in terms of a probabilistic model which defines the data generating process.Our approach extends the basic ideas from Cazals, Florens and Simar (2002) to thefull multivariate case. We introduce the concepts of conditional efficiency measure andof conditional efficiency measure of order-m. Afterwards we suggest a practical wayfor computing the nonparametric estimators. Finally, a simple methodology to investigatethe influence of these external factors on the production process is proposed.Numerical illustrations through some simulated examples and through a real data seton Mutual Funds show the usefulness of the approach.
Keywords: 330; production function; frontier; nonparametric estimation; environmental factors; robust estimation; Produktionsfunktion; Nichtparametrisches Verfahren; Umwelt; Data-Envelopment-Analyse; Robustes Verfahren; Theorie